A straightforward strategy for reducing variability in flowering time at warm ambient temperatures. (31st December 2023) - Kim, Sol-Bi; Jung, Jae-Hoon
ABSTRACT: Ambient temperature is one of the major environmental factors affecting flowering. As the temperature rises, most plants, including Arabidopsis, flower more rapidly. In addition, phenotypic variability in flowering time tends to increase at warm ambient temperatures. The increased variability of flowering time at warm temperatures prevents accurate flowering time measurements, particularly when evaluating the flowering time of Arabidopsis plants under short-day conditions in order to restrict the photoperiodic effect. Here, we propose a simple method for reducing the variability of flowering time at warm temperatures. Instead of growing plants at different temperatures from germination, the strategy of first vegetative growth at cool temperatures and then shifting to warm temperatures allows plants to respond more stably and robustly to warm temperatures. Consistent with flowering time measurements, plants grown under the modified growth condition exhibited higher levels of FLOWERING LOCUS T ( FT ) gene expression than plants grown exclusively at warm temperatures. This approach enables more precise thermo-response studies of flowering time control in Arabidopsis .